Surgical site infection after hip replacement due to a novel Peptoniphilus species, provisionally named 'Peptoniphilus nemausus' sp. nov. (February 2020) - Enault, Cécilia; Aujoulat, Fabien; Pantel, Alix; Cellier, Nicolas; Lechiche, Catherine; Mégy, Bernard; Lavigne, Jean-Philippe; Marchandin, Hélène
Abstract: We report a case of surgical site infection after total hip prosthesis replacement due to an ofloxacin-resistant Peptoniphilus isolate belonging to an unknown species for which the name ' Peptoniphilus nemausus ' sp. nov. is proposed. Follow-up was favourable under clindamycin and rifampin for 3 months in this patient whom had a Proteus mirabilis infection treated by fluoroquinolone. Highlights: Unusual case of monomicrobial Peptoniphilus surgical site infection. A novel species is proposed in the genus: ' Peptoniphilus nemausus ' sp. nov. Probable selection by previous ofloxacin treatment due to high-level resistance.